Optimal Contracting, Corporate Finance, and Valuation with Inalienable Human Capital - BOLTON, PATRICK; WANG, NENG; YANG, JINQIANG (Journal of Finance, 2019)
ABSTRACT A risk‐averse entrepreneur with access to a profitable venture needs to raise funds from investors. She cannot indefinitely commit her human capital to the venture, which limits the firm's debt capacity, distorts investment and compensation, and constrains the entrepreneur's risk sharing. This puts dynamic liquidity and state‐contingent risk allocation at the center of corporate financial management. The firm balances mean‐variance investment efficiency and the preservation of financial slack. We show that in general the entrepreneur's net worth is overexposed to idiosyncratic risk and underexposed to systematic risk. These distortions are greater the closer the firm is to exhausting its debt capacity.